A phase 2, randomized, double‐blind, multicenter study comparing siltuximab plus best supportive care (BSC) with placebo plus BSC in anemic patients with International Prognostic Scoring System low‐ or intermediate‐1–risk myelodysplastic syndrome. Issue 9 (23rd June 2014) - Garcia‐Manero, Guillermo; Gartenberg, Gary; Steensma, David P.; Schipperus, Martin R.; Breems, Dimitri A.; de Paz, Raquel; Valcárcel, David; Kranenburg, Britte; Reddy, Manjula; Komrokji, Rami S.
<x xml:space="preserve">Abstract</x> Interleukin‐6 (IL‐6) may play an important role in the pathophysiology of anemia of inflammation associated with myelodysplastic syndrome (MDS). This double‐blind, placebo‐controlled, phase 2 study assessed the efficacy and safety of siltuximab, a chimeric anti–IL‐6 monoclonal antibody, in patients with low‐ and intermediate‐1–risk MDS who require transfusions for MDS anemia. Patients were randomized in a 2:1 ratio to siltuximab 15 mg kg−1 every 4 weeks + best supportive care (BSC) or placebo + BSC for 12 weeks. The primary endpoint was reduction in red blood cell (RBC) transfusions to treat MDS anemia, defined as ≥50% relative decrease and ≥2‐unit absolute decrease in RBC transfusions. Fifty and 26 patients were randomized to the siltuximab and placebo groups, respectively. The study did not meet its prespecified hypothesis, with six (12%) patients in the siltuximab group and one (3.8%) in the placebo group having reductions in RBC transfusions (P = 0.271). At the time of the planned futility analysis, the prespecified cutoff criteria were not met, and the study was terminated early due to lack of efficacy. No unexpected safety findings were observed. In conclusion, compared to placebo, treatment with siltuximab did not reduce RBC transfusions in transfusion‐dependent patients with low‐ and intermediate‐1–risk MDS. Future studies might explore siltuximab in patients with less iron overload and with elevated IL‐6 levels and/or using higher doses for MDS. Am. J. Hematol. 89:E156–E162, 2014. © 2014 Wiley Periodicals, Inc.